Applications of heat acclimation for competitive sport performance - Daanen, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It is well established that competition in the heat without sufficient heat acclimation (HA) prior to the event leads to suboptimal performance. It is however less clear how the period of heat acclimation interferes with the tapering process. Methods: The literature describing experiments regarding de-acclimation and re-acclimation is reviewed with special focus on the duration of physiological process changes and compared to the literature on tapering. Results: In contrast to common belief, several papers (e.g. Weller et al., 2007; Daanen et al. 2011) show that the positive effects of HA are maintained for at least a month, and that the full state of HA can be reestablished in only 3 days of re-acclimation. Discussion: The finding that HA is maintained for a long period of time enables the reduction of exercise intensity several weeks prior to the event in the heat. Thus, the recommendations to taper for 8-14 days (LeMeur et al. (2012)) can be accommodated. It is, however, recommended to reserve a few days for re-acclimation just prior to the event.